Аутсорсинг в умовах віддаленої роботи - Маковоз, Оксана Сергіївна; Крючко, О. М. (Причорноморський науково-дослідний інститут економіки та інновацій, 2024)
Аутсорсинг в умовах віддаленої роботи став ключовим інструментом для оптимізації бізнес-процесів та зниження витрат. Війна в Україні підкреслила важливість аутсорсингу, особливо в енергетичній сфері, де віддалена робота допомагає забезпечувати безперервність операцій та підвищувати ефективність. Особлива увага приділяється відновлюваним джерелам енергії, які, незважаючи на виклики, залишаються пріоритетом для України. Виклики включають необхідність фізичної присутності для ремонту та технічного обслуговування. Рекомендації дослідження включають розвиток інфраструктури для підтримки віддаленої роботи, інвестиції у технології, розширення міжнародного співробітництва та створення умов для залучення інвестицій у відновлювану енергетику. Аутсорсинг має потенціал для зміцнення економічної стійкості України під час війни та у післявоєнний період.

Outsourcing in the context of remote work has become a crucial tool for optimizing business processes and reducing costs. The war in Ukraine has highlighted the importance of outsourcing, particularly in the energy sector, where remote work helps ensure operational continuity and increase efficiency. Special attention is given to renewable energy sources, which remain a priority for Ukraine despite challenges. The challenges include the necessity of physical presence for maintenance and repair. The study's recommendations include developing infrastructure to support remote work, investing in technology, expanding international cooperation, and creating conditions for attracting investments in renewable energy. Outsourcing has the potential to enhance Ukraine's economic resilience during the war and in the post-war period. The study emphasizes the transformation of outsourcing from a simple delegation of tasks to a strategic tool for businesses. Business Process Outsourcing (BPO) has evolved into an entire industry that supports other companies by delegating tasks to external organizations, making processes more efficient. In times of crisis, such as war, outsourcing becomes critical for maintaining business processes, ensuring competitiveness, and effectively responding to new challenges. The war has significantly impacted Ukraine's energy sector, presenting challenges but also opportunities for outsourcing development. Renewable energy projects, such as solar and wind, continue to receive support and investments, despite the conflict. The restoration plan for Ukraine includes substantial investments in green energy development, highlighting the importance of renewable sources. The energy sector actively utilizes consulting and analytics services through outsourcing, enhancing safety and efficiency. Physical tasks related to maintenance and repair remain challenging due to the need for on-site presence, especially in conflict zones. The study concludes that outsourcing in Ukraine's energy sector has significant potential, particularly in renewable energy and consulting services, while acknowledging the limitations for physical maintenance work. The study recommends developing remote work infrastructure, investing in technology, and fostering international cooperation to support outsourcing and attract investments, ultimately contributing to Ukraine's economic resilience and post-war recovery.
Outsourcing in conditions of teleworking
Keywords: управління; аутсорсинг; віддалена робота; аутсорсинг бізнес-процесів; енергетична сфера; teleworking; outsourcing; key advantages of outsourcing; energy sector; business process outsourcing; renewable energy sources; wartime conditions